Field Efficacy of Three Botanical Insecticide Formulations a gainst Tomato insect pest ,White fly Bemisia tabaci (Genn) ( Hemiptera : Aleyrodidae) in Khartoum State. - Suliman, D.Ashwag Ahmed Mohammed; Kheir, D.Saif Eldien Mohammed (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Field Efficacy trial of three Botanical insecticide Formulations were conducted on tomato crop during 2006/2007 and 2007/2008 seasons in Khartoum State, Shambat, Sudan University of Science and Technology, Sudan, to assess the effectiveness of these formulations in reducing population of one of the major Tomato pest, white fly on tomato . The Efficacy of Three Botanical Insecticide Formulations, Neem -seedkernel(Azadrachta indica) hexane extract at 2.5%, Cotton-seed-kernel (Gossypium hirsutum) hexane extract at 2.5% and Argel leaves (Solenostemma argel) aqueous extract at 37.3g/6L were compared to a synthetic insecticide Actara 40g at the rate of 0.75 L/F as (standard). The application of Neem, Cotton and Argel decrease population of WF and the treatment of Actara gave the best performance in all cases, causing 79.55% and 92.86% drop in whitefly population relative to the pre-sp.c. after 48hrs from application,at season 2006/ 2007 and season 2007/2008 respectively. Neem was the second best with 74.19% and 91.67% drop in whitefly population , followed by Cotton as the third best with 37.50% and 77.78 % drop in whitefly population Whereas Argel was the lowest recorded as 16.00% and 64.52% drop in whitefly . also the application of Argel indicated a positive and significant effect on the fruit set and yield gave highly weight fruit of tomato (6.70 g/ plant) compared with minimum for all parameters 4.28 g/ plant which obtained in control in nine picks at season 2006/2007, it is suggested that further research can be conducted to observe the hormonal effect of Argel on fruit set, yield and fruit guality of tomatoes.